Original paperThe relation of autologous serum and plasma skin test results with urticarial activity score, sex and age in patients with chronic urticaria - Aktar, Sirac; Akdeniz, Necmettin; Ozkol, Hatice Uce; Calka, Omer; Karadag, Ayse (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction: Some previous studies reported autoimmunity as an etiologic factor in chronic urticaria (CU), but the results of some autoimmunity tests in these studies are conflicting. Aim : To concretize whether there was any relation of autologous serum skin test (ASST) and autologous plasma skin test (APST) results with sex, age and urticarial activity score (UAS) in patients with CU. Material and methods : Fifty patients with CU and twenty healthy subjects admitted to our dermatology clinic were included in the present study. The ASST and APST were applied to all individuals. Results : The positiveness rates of ASST and APST were significantly higher in the patient group than controls (p = 0.027, p = 0.001, respectively). Among patients, the APST positiveness rate (72%) was significantly (p < 0.05) higher than ASST (46%). It was seen that 48% of patients with negative ASST results had positive APST. However, no patient with negative APST results had positive ASST. There were significant (p < 0.05) relations of the tests’ positiveness rates with sex and old age but with UAS. The diameter of the erythematous papule was remarkably (p < 0.05) larger in APST than ASST and also significantly (p < 0.05) larger in females compared to males in both tests (p < 0.05). It was positively increased with old age (p < 0.05). Conclusions : We can suggest that APST is more sensitive than ASST in the assessment of autoimmunity in CU. A high positiveness rate of APST results may be attributed to high numbers of autoantibodies and coagulation factors present in plasma that might probably play a role in etiopathogenesis of CU.